JENIS PERSALINAN DENGAN SKALA NYERI INVOLUSI UTERUS MASA NIFAS DI RSUD Prof. Dr. SOEKANDAR MOJOSARI MOJOKERTO - Amalia, Ana; Mafticha, Elyana (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2012)
Pain in childbirth, often makes mothers give to birth normally. Many mothers who decide to do the cesarean section after a normal birth half way through, so this study to identify the type of labor with a pain scale of involution of the uterus during childbirth in hospitals Prof. Dr. Soekandar Mojosari Mojokerto.Type of the Analytic Observational study with cross sectional design. The population in this study were postpartum mothers at delivery and Caesarean section deliveries in hospitals normally the first day of Prof. Dr. Soekandar Mojosari Mojokerto. Population of 37 people. Sampling technique with the purposive sampling method. Collecting data using questionnaires. Data processing techniques through Editing, Coding, Tabulating. The research was conducted on May 22 to June 7.The results that are almost entirely in pain with uterine involution category Very Painful but can still be controlled on the type of cesarean section delivery of 20 respondents (54.1%), and none who have pain with uterine involution category Very Painful but can still be controlled in labor normal. Mean values recorded for the type of cesarean section delivery is greater than the normal type of labor (23.56> 6.70). Results Statistical 0.00 <0.05 hence H0 refused and H1 accepted that there is a relationship between type of delivery with a pain scale involution of the uterus during childbirth in hospitals Prof. Dr. Soekandar Mojosari Mojokerto.Normal type of labor will reduce the pain scale involution of the uterus during childbirth, along with a range of factors that exist, namely age and parity.In this study the uterine involution pain scale on the type of cesarean delivery cesarean delivery is higher than normal. This is because the wound incision in cesarean section deliveries increase the intensity of pain during childbirth uterine involution. Health workers are expected to provide new information on uterine involution pain scale on each type of labor.Keyword: Type of Labor, Pain Scale.